PERSEPSI MASYARAKAT TERHADAP KINERJA APARATUR DESA CIJENUK KECAMATAN CIPONGKOR DALAM PENYELENGGARAAN PELAYANAN PUBLIK - , Muhamad Daffa Nugraha (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
Currently, many people feel that the performance of the village government has not reached an optimal level. This study aims to evaluate the public's views on the performance of the village government in providing public services, focusing on Cijenuk Village in Cipongkor District, West Bandung Regency. The research method used is a quantitative descriptive method, with respondents who are residents of Cijenuk Village. Data collection was carried out through the use of questionnaires. The independent variable (X) in this study is public perception, while the dependent variable (Y) is the performance of the village government. The results of the analysis show scores that can generally be considered good, but the findings of the correlation between public perceptions of the performance of the village government in providing public services in Cijenuk Village are categorized as less good.